How much force is required to perforate a colon during colonoscopy? An experimental study. (March 2019) - Johnson, Steve; Schultz, Michael; Scholze, Mario; Smith, Troy; Woodfield, John; Hammer, Niels
Abstract: Introduction: Colonoscopy is a commonly-performed procedure to diagnose pathology of the large intestine. Perforation of the colon is a rare but feared complication. It is currently unclear how much force is actually required to cause such injury nor how this is altered in certain diseases. Our aim was to analyze the forces required to perforate the colon in experiments using porcine tissues. Methods: Using 3D printing technology, models of two commercially available colonoscope heads were printed under three configurations: straight (I), 90°- bent (L) and fully bent (U). Samples of porcine colon were assessed with the models and configurations under perpendicular and angular load application and these data compared to the maximum force typically exerted by experienced colonoscopists. Results: The force required for perforation was significantly lower for the I compared to the L of the larger colonoscope head configuration under angular loading (14.1 vs. 46.5 N). Similar differences were found for linear stiffness when loaded (I vs. L small when loaded perpendicular: 0.8 vs. 2.4 N/mm, I vs. L large when loaded angled 0.7 vs. 2.1 N/mm). The mode and site of failure varied significantly between the scopes, with delamination of the mucosa/submucosa below the sample (96%) for the I, blunt mucosa/submucosa/muscularis failure adjacent to the loading site (77%) for the L, and failure of all colon layers lateral to the loading site (59%) for the U configuration, respectively. Perpendicular and angulated loading resulted in similar load-deformation values. Maximum forces typically exerted by colonoscopists averaged 13.9–27.9 N, depending on the colonoscope model and head configuration. Discussion: The force required for colon perforation varies depending on the type mode of loading and is likely lower than the force an experienced colonoscopist would exert in daily practice. There is a real risk of perforation, especially when the end of the scope is advancing directly into the colonic wall. The given experimental setup allowed to obtain reliable data of the colon in a standardized scenario, forming the basis for further experiments.